S98 The effects of BMPRII loss on endothelial shear adaptation in the pulmonary vascular endothelium. (12th November 2019) - Mahomed, AS; Burke-Gaffney, A; Moledina, S; Wort, SJ
Abstract : Introduction: Abnormal endothelial morphological adaptation to shear stress is a feature of pulmonary arterial hypertension (PAH) but the mechanisms responsible are poorly understood. In this study, we explored whether BMPRII loss mediates abnormal human pulmonary artery endothelial cell (HPAEC) adaptation to laminar shear stress and investigate gene expression of shear-sensitive Rho GTPases (RhoA, Rac1 and CDC42), known for their involvement in cytoskeletal reorganisation. Methods: HPAECs were transfected with BMPRII siRNA (siBMPRII) or control siRNA (siControl). Laminar shear stress acting on HPAECs was modelled using a parallel-plate fluid flow chamber (ibdi). siControl and siBMPRII-transfected HPAECs were exposed to unidirectional shear stress (15 dyn/cm 2 ) for 72 hours. Phase-contrast and confocal microscopy were used to assess cell morphology and orientation. Gene expression of RhoA, Rac1 and CDC42 were quantified using qPCR. Results: siControl-transfected HPAECs subjected to shear stress significantly elongated (length-to-width ratio 1.90±0.227 versus 4.12±0.133, p< 0.001 ) and aligned within the direction of flow (31.7±4.82% versus 62.9±5.83%, p< 0.05 ) compared with static siControl cultures, whereas that of BMPRII-silenced HPAECs exposed to flow failed to significantly elongate (1.79±0.173 versus 2.45±0.136) and align (29.6±1.97% versus 42.1±5.49%), relative to static siBMPRII HPAECs. Shear stress significantly induced the upregulation of RhoA and not Rac1 and CDC42 in siControl-transfected HPAECs, while siBMPRII-treated HPAECs subjected to flow did not exhibit significant increases in RhoA, Rac1 and CDC42 mRNA, in comparison with static counterparts, respectively. Conclusion: Inactivating mutations in the BMPRII gene may contribute to PAH by engendering abnormal pulmonary artery endothelial shear adaptation.